65.7k views
2 votes
Find thd
(dy)/(dx) : x³y²+sin(x㏑y)+
e^(xy)=0

User Mansi
by
4.9k points

1 Answer

3 votes


x^3y^2+\sin(x\ln y)+e^(xy)=0

Differentiate both sides, treating
y as a function of
x. Let's take it one term at a time.

Power, product and chain rules:


(\mathrm d(x^3y^2))/(\mathrm dx)=(\mathrm d(x^3))/(\mathrm dx)y^2+x^3(\mathrm d(y^2))/(\mathrm dx)


=3x^2y^2+x^3(2y)(\mathrm dy)/(\mathrm dx)


=3x^2y^2+6x^3y(\mathrm dy)/(\mathrm dx)

Product and chain rules:


(\mathrm d(\sin(x\ln y))/(\mathrm dx)=\cos(x\ln y)(\mathrm d(x\ln y))/(\mathrm dx)


=\cos(x\ln y)\left((\mathrm d(x))/(\mathrm dx)\ln y+x(\mathrm d(\ln y))/(\mathrm dx)\right)


=\cos(x\ln y)\left(\ln y+\frac1y(\mathrm dy)/(\mathrm dx)\right)


=\cos(x\ln y)\ln y+\frac{\cos(x\ln y)}y(\mathrm dy)/(\mathrm dx)

Product and chain rules:


(\mathrm d(e^(xy)))/(\mathrm dx)=e^(xy)(\mathrm d(xy))/(\mathrm dx)


=e^(xy)\left((\mathrm d(x))/(\mathrm dx)y+x(\mathrm d(y))/(\mathrm dx)\right)


=e^(xy)\left(y+x(\mathrm dy)/(\mathrm dx)\right)


=ye^(xy)+xe^(xy)(\mathrm dy)/(\mathrm dx)

The derivative of 0 is, of course, 0. So we have, upon differentiating everything,


3x^2y^2+6x^3y(\mathrm dy)/(\mathrm dx)+\cos(x\ln y)\ln y+\frac{\cos(x\ln y)}y(\mathrm dy)/(\mathrm dx)+ye^(xy)+xe^(xy)(\mathrm dy)/(\mathrm dx)=0

Isolate the derivative, and solve for it:


\left(6x^3y+\frac{\cos(x\ln y)}y+xe^(xy)\right)(\mathrm dy)/(\mathrm dx)=-\left(3x^2y^2+\cos(x\ln y)\ln y-ye^(xy)\right)


(\mathrm dy)/(\mathrm dx)=-\frac{3x^2y^2+\cos(x\ln y)\ln y-ye^(xy)}{6x^3y+\frac{\cos(x\ln y)}y+xe^(xy)}

(See comment below; all the 6s should be 2s)

We can simplify this a bit by multiplying the numerator and denominator by
y to get rid of that fraction in the denominator.


(\mathrm dy)/(\mathrm dx)=-(3x^2y^3+y\cos(x\ln y)\ln y-y^2e^(xy))/(6x^3y^2+\cos(x\ln y)+xye^(xy))

User Dexter Huinda
by
5.1k points